Analisis Konten Tiktok Terhadap Motivasi Belajar Siswa Sekolah Dasar - Anisa Anisa; Desty Endrawati Subroto; Anggun Mutia; Imas Purnamasari; Tarsih Tarsih (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to explore how TikTok content is related to elementary school students' learning motivation. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation from five students, three teachers, and two student guardians at SDN 02 Serang. The results show that TikTok content has mixed effects on students' learning motivation; some students feel motivated by educational content, while others experience a decline in learning enthusiasm due to watching too much entertainment content. In addition, TikTok also plays a role in shaping students' social aspects, such as self-confidence and interaction skills. Proper mentoring is needed so that the use of TikTok can optimally support the learning process.